Improving mortality profile analysis in zooarchaeology: a revised zoning for ternary diagrams. (June 2015) - Discamps, Emmanuel; Costamagno, Sandrine
Abstract: Mortality profiles have figured prominently among tools used by zooarchaeologists to investigate relationships between hominids and prey species. Their analysis and interpretation have been considerably influenced by M.C. Stiner's approach based on ternary diagrams. Part of this method included the demarcation of "zones" in ternary diagrams identifying specific mortality patterns (e.g. attritional, catastrophic, prime-dominated, etc.). Since its introduction some twenty-five years ago, this zoning has, however, received little critical attention. Mathematical modelling as well as a reassessment of the ecological data used to define these zones reveal several problems that may bias interpretations of mortality profiles on ternary diagrams. Here we propose new, mathematically supported definitions for the zoning of ternary diagrams combined with species-specific age class boundaries based on ethological and ontological data for seven of the most common hominid prey (bison, red deer, reindeer, horse, zebras, African buffalo and common eland). We advocate for the use of new areas (JPO, JOP, O and P zones) that produce more valid interpretations of the relative abundance of juveniles, prime and old adults in an assemblage. These results contribute to the improvement of the commonly used method of mortality profile analysis first advanced by M.C. Stiner. Graphical abstract: Highlights: Identification of specific mortality patterns may rely on zones in ternary plots. Commonly used zoning of ternary diagrams is shown to be unreliable. New mathematically supported definitions for the zoning of ternary diagrams. Species-specific age class boundaries are suggested for 7 species.